Synergistic warming- and catchment-driven mid-Holocene cyanobacterial development: Pigment evidence from shallow eutrophic Lake Mayinghai on the Chinese Loess Plateau - Zhang, Xiaosen; Su, Ling; Zhang, Jingyue; Shen, Zhongwei; Zhang, Shengrui; Xu, Qinghai; Liu, Jianbao (Frontiers in Earth Science, 2023)
The current lake environmental problem of harmful cyanobacterial blooms cannot be mitigated effectively despite numerous eutrophication control strategies, and climate warming may have been considered as a potential key driver. However, it is still unclear how climate change and associated natural processes influence cyanobacterial development. Here we use a sedimentary pigment record from a remote, alpine, small and eutrophic lake (Lake Mayinghai) on the Chinese Loess Plateau and take the mid-Holocene as an analog to explore the possible influences of temperature, precipitation and terrestrial vegetation on in-lake and catchment processes, algal compositional changes and cyanobacterial development. The pigment data indirectly suggest that a distinctly low β-carotene to chlorophyll a ratio during the mid-Holocene is likely due to an increase in non-nitrogen-fixing colonial coccoid cyanobacteria at the expense of nitrogen-fixing filamentous cyanobacteria. There are two probable synergistic driving mechanisms, of which one is high temperatures and associated increased lake thermal stratification and the other is high inorganic nitrogen supply and resultant increased lake nitrogen to phosphorus ratio. This study provides implications for the potential influences of future climate change on cyanobacterial development under a warmer, wetter and re-forested environment on the Chinese Loess Plateau.